2007
DOI: 10.1016/j.jecp.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The development of facial emotion recognition: The role of configural information

Abstract: The development of children's ability to recognize facial emotions and the role of configural informationin this development were investigated. In the study, 100 5-, 7-, 9-, and 11-year-olds and 26 adultsneeded to recognize the emotion displayed by upright and upside-down faces. The same participantsneeded to recognize the emotion displayed by the top half of an upright or upside-down face that was orwas not aligned with a bottom half that displayed another emotion. The results showed that the ability torecogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
253
4
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(305 citation statements)
references
References 44 publications
38
253
4
10
Order By: Relevance
“…However, results from our behavioral data indicate that impairments in top-down control may affect emotional face processing circuitry differentially depending on emotional valence. This is consistent with extant literature indicating that developmental trajectories for emotional face processing are valence-specific even in typical development, including evidence that happy faces are recognized at an earlier age, are automatically and more rapidly processed in childhood, require fewer cognitive resources overall, and less prefrontal cortical recruitment in particular (Batty and Taylor, 2006;Yurgelun-Todd and Killgore, 2006;Durand et al, 2007;Gao and Maurer, 2010). Therefore, it is possible that negative expressions such as fearful face stimuli may require increased recruitment of dorsal prefrontal modulatory regions for higher order emotional face processing, and as such, are more affected than other emotions in TS.…”
Section: Discussionsupporting
confidence: 90%
“…However, results from our behavioral data indicate that impairments in top-down control may affect emotional face processing circuitry differentially depending on emotional valence. This is consistent with extant literature indicating that developmental trajectories for emotional face processing are valence-specific even in typical development, including evidence that happy faces are recognized at an earlier age, are automatically and more rapidly processed in childhood, require fewer cognitive resources overall, and less prefrontal cortical recruitment in particular (Batty and Taylor, 2006;Yurgelun-Todd and Killgore, 2006;Durand et al, 2007;Gao and Maurer, 2010). Therefore, it is possible that negative expressions such as fearful face stimuli may require increased recruitment of dorsal prefrontal modulatory regions for higher order emotional face processing, and as such, are more affected than other emotions in TS.…”
Section: Discussionsupporting
confidence: 90%
“…For example, de Heering and colleagues (2007) found that 4-, 5-and 6-year-olds displayed similar susceptibility to each other and to adults when tested using the original matching procedure (see also Carey & Diamond, 1994;Mondloch, Pathman, Maurer, Le Grand, & de Schonen, 2007;Susilo, Crookes, McKone, & Turner, 2009). Comparable results have also been reported for expression composites (Durand, Gallay, Seigneuric, Robichon, & Baudouin, 2007). Susceptibility, however, may be present at an even younger age.…”
Section: Developmentmentioning
confidence: 94%
“…First, the literature is inconsistent with respect to the relationship between individuals' susceptibility to the composite face illusion and other markers of holistic representation, including the part-whole (Tanaka & Farah, 1993) and face-inversion (Yin, 1969) effects. Whilst some authors have found associations between these measures using the complete design (DeGutis, Wilmer, Mercado, & Cohan, 2013), others using the original matching procedure have not (Durand et al, 2007;Wang, Li, Fang, Tian, & Liu, 2012). For example, Wang and colleagues (2012) found susceptibility to the composite and part-whole effects were unrelated.…”
Section: The Functional Significance Of the Composite Face Illusionmentioning
confidence: 99%
“…We also examined age-or gender-related differences in MAAC responses. These were exploratory analyses with no a priori hypotheses, though previous studies suggest that emotion recognition improves with age in nonclinical children [21,22], and that nonclinical preschool and school-aged girls may have a more accurate emotional understanding than their male counterparts [23,24].…”
Section: Introductionmentioning
confidence: 99%